Professor Halina Szwarc - the creator of Universities of the Third Age in Poland - Józef Półturzycki (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
The article reminds a profile of Professor Halina Szwarc (1923-2002), who is one of the most outstanding Polish andragogists, being a creator of the concept of a university of the third age in Poland, whose realisation was the third educational facility of this type in the world. The text makes references to her origins and childhood. Her heroic conspiracy activity which she started in 1939, being only 16, is presented. Her life in the post-war period is presented, focusing above all on her scientific and professional career, but not omitting personal threads. Much attention is given to her efforts made in founding the University of the Third Age in Warsaw, to which she gave broad goals and tasks, as well as forms of activity. The article is ended with an appeal to the contemporary figures of the world of science for a permanent remembrance and recognition for Professor Szwarc and following her example.